A Critical Appraisal of the Dark-Triad Literature and Suggestions for Moving Forward. (August 2019) - Miller, Joshua D.; Vize, Colin; Crowe, Michael L.; Lynam, Donald R.
Since its introduction in 2002, dark-triad research—the simultaneous study of psychopathy, narcissism, and Machiavellianism—has exploded, with the publication of hundreds of peer-reviewed articles, books, and chapters, as well as coverage by the lay media. Unfortunately, several limitations to this research are unrecognized or ignored. These limitations include (a) the treatment of dark-triad constructs as unidimensional, contrary to evidence for their multidimensionality; (b) the indistinctness between current measures of Machiavellianism and psychopathy; (c) the use of multivariate statistical approaches that pose statistical and interpretive difficulties; (d) failure to test dark-triad relations directly against one another; and (e) methodological concerns related to convenience sampling and reliance on mono-method approaches. We discuss these problems in detail and describe solutions that can result in a more robust, replicable, and meaningful literature moving forward.